2020
DOI: 10.1093/intimm/dxaa063
|View full text |Cite
|
Sign up to set email alerts
|

AMBRA1 controls antigen-driven activation and proliferation of naive T cells

Abstract: AMBRA1 is a member of the BECN1 (BECLIN1) complex protein, and it plays a role in autophagy, cell death, tumorigenesis, and proliferation. We recently reported that on TCR stimulation, AMBRA1 controlled both autophagy and the cell cycle with metabolic regulation. Accumulating evidence has shown that autophagy and metabolic control are pivotal for T cell activation, clonal expansion, and effector/memory cell fate decision. However, it is unknown whether AMBRA1 is involved in T cell function under physiological … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 40 publications
0
1
0
Order By: Relevance
“…found that AMBRA1 regulates the activity of OVA53 precursor T cells and naive T cells in an autophagy-dependent manner ( 91 ). Furthermore, this group also found that AMBRA1 regulates the proliferation of precursor T cells and naive T cells in an autophagy-independent manner ( 92 ). This regulation might be attributed to the recent finding that CULLIN4–AMBRA1 E3 ligase regulates the stability of cyclin D to control the cell cycle ( 35 ).…”
Section: Ambra1—a Potential Target For Anticancer Therapymentioning
confidence: 98%
“…found that AMBRA1 regulates the activity of OVA53 precursor T cells and naive T cells in an autophagy-dependent manner ( 91 ). Furthermore, this group also found that AMBRA1 regulates the proliferation of precursor T cells and naive T cells in an autophagy-independent manner ( 92 ). This regulation might be attributed to the recent finding that CULLIN4–AMBRA1 E3 ligase regulates the stability of cyclin D to control the cell cycle ( 35 ).…”
Section: Ambra1—a Potential Target For Anticancer Therapymentioning
confidence: 98%